Peran Guru Dalam Meningkatkan Motivasi Belajar Siswa Di Era Digital - Fatin Syahirah; Futhri Raudhatul Kabry; Geniza Aidilla Syuaira; Naffa Qaila Dalimunthe; Said Hasian Simanjuntak; Inom Nasution (Universitas Maritim AMNI Semarang, 2023)
This research explores the dynamics of teaching and learning in the Digital Era, making a significant contribution to discussions regarding the position of education in facing changing times and the digital era. Through literature research, it was found that learning in the digital era has unique characteristics, especially because today's students are the digital native generation. They were born, grew, and developed in a digital environment, creating differences in the way they obtain information compared to previous generations. Therefore, teachers, as partners in the learning process, need to have the ability to design learning activities that enable students to obtain information effectively in the context of limited time. Learning motivation reflects students' internal drive to achieve learning goals. Motivation has a crucial role in student enthusiasm, and support from teachers is an important supporting factor. Teachers have a role in improving the quality of education by providing motivation to students. The success of the learning process depends on the level of student motivation. To achieve optimal learning outcomes, teachers need to use creativity in motivating students by presenting innovative and creative learning activities.